Aleister Crowley on Drugs. (14th September 2016) - Partridge, Christopher
Abstract : While much has been written about the life, work and influence of Aleister Crowley, relatively little attention has been directed to his drug use. This is a little surprising because, not only did he become addicted to heroin, but he incorporated psychoactive substances in his occult work, discussed their psychological effects, commented on drug-related social issues, critiqued contemporary drug legislation, published drug literature, and even translated Charles Baudelaire's "Poem of Hashish." This article discusses his thought on drugs and religious experience and suggests that they were, largely because of his addiction, a more important force in his life than has thus far been acknowledged.